Carbazole-based compounds containing aldehyde and cyanoacetic acid: optical properties and applications in photopolymerization. Issue 87 (5th December 2017) - Abro, Hussain Ahmed; Zhou, Tengfei; Han, Weixiang; Xue, Tanlong; Wang, Tao
Abstract : Carbazole-based aldehyde and cyanoacetic acid containing dyes were synthesized and applied as photosensitizers in photopolymerization with a LED light source at 455 nm. Abstract : Carbazole-based dyes containing aldehyde and cyanoacetic acid groups were synthesized through Sonogashira coupling and Knoevenagel reactions. These compounds included 6-((4-(diphenylamino)phenyl)ethynyl)-9-ethyl-9 H -carbazole-3-carbaldehyde (CCC), 9-ethyl-6-((9-ethyl-9 H -carbazol-3-yl)ethynyl)-9 H -carbazole-3-carbaldehyde (TCC), ( E )-2-cyano-3-(9-ethyl-6-((9-ethyl-9 H -carbazol-3-yl)ethynyl)-9 H -carbazol-3-yl)acrylic acid (CCN) and ( E )-2-cyano-3-(6-((4-(diphenylamino)phenyl)ethynyl)-9-ethyl-9 H -carbazol-3-yl)acrylic acid (TCN). Density functional theory (DFT) calculations revealed these structures to be coplanar-conjugated molecular and uniform in shape. The UV spectra showed three main absorption peaks from 240 nm to 400 nm, indicating π–π* and n–π* electron transitions. The calculated vertical singlet excitation energy was within the range of n–π*. This finding was confirmed based on the acceptor results in reduced highest occupied molecular orbital-lowest unoccupied molecular orbital gap by launching cyanoacetic acid. These functional compounds could be used as dyes/photosensitizers.